<< . .

. 3
( : 3)



= 0 + 0 + 0 + (2*2) + 1 = 5 .

= 0 + 0 + 3 + 2 + 0 = 5 .

= 0 + 0 + 0 + 0 + 1 = 1 .

= 5 + 0 + 0 + 2 + 1 =8 .

= (2*5) + 0 + 3 + 0 + 0 = 13 .

= (2*5) + 4 + 3 + 0 + 1 = 18 .

= 0 + 0 + 0 + 0 + 0 = 0 .

= (2*5) + 0 + 0 + 0 + 1 =11 .

= 0 + (2*4) + 3 + 0 + 0 = 11 .

= (2*5) + (2*4) + 3 + 2 + 0 =23 .

= 0 + 0 + 0 + 0 + 1 = 1 .


p, pp :

----------------------------------------------------------------------
| .| | p.| .| p| .|.|.|.| p| p.|
|------|-----|------|-----|-----|-----|-----|-----|-----|-----|------|
| - 5 | - 5 | - 1 | - 8 | -13 | - 18| - 0 | - 11| - 11| - 23| - 1 |
----------------------------------------------------------------------

4. p p .
----------------------------------------------------
p p p p , - - . p :

----------------------------------------------------------------------
| .| | p.| .| p| .|.|.|.| p| p.|
|------|-----|------|-----|-----|-----|-----|-----|-----|-----|------|
| + 14 | + 2 | + 12 | + 9 | +11 | + 12| + 5 | + 4 | + 9 | + 7 | + 6 |
|------|-----|------|-----|-----|-----|-----|-----|-----|-----|------|
| - 5 | - 5 | - 1 | - 8 | -13 | - 18| - 0 | - 11| - 11| - 23| - 1 |
|------|-----|------|-----|-----|-----|-----|-----|-----|-----|------|
| | | | | | | | | | | |
| + 9 | - 3 | + 11 | + 1 | - 2 | - 6 | + 5 | - 7 | - 2 | - 16| + 5 |
| | | | | | | | | | | |
----------------------------------------------------------------------

p , p p, , - .

, (p ) ("p ").

, p (p p), (" ").

pp pp :

- pp (+ 11 ).
p - p (- 16 ).
pp - , p, p, pp.
pp - , p, p, , .


<< . .

. 3
( : 3)